Desarrollo de resistencia al hongo botritis cinerea en el cultivo de rosas (rosa sp) mediante la aplicación de cuatro niveles de potasio en la zona de Cayambe Provincia de Pichincha. - González Flores, Jorge Vinicio (2011)
The present investigation treated itself about the " Development of Resistance to the Mushroom Botritis cinerea in the culture of Roses (Rose sp) By means of the application of three levels of potassium there is located in the sector Santa Rosa of the Company, parish Ayora, canton Cayambe, province of Bargain. The design of blocks was in use completely at random, the analysis of variance was calculated and the treatments were differing by means of Tukey's test to 5 %. The number of plants used in the investigation was of 4650, with 15 experimental units and 10 it plants for experimental unit chosen at random. One used four doses of fertilizer Muriato of potassium KCL whose applications treatment fulfilled weekly, the doses treatment 1 (2 gr/l), 2 (3 gr/l), treatment 3 (4 gr/l), treatment 4 (5 gr/l).